Socioeconomic Risk Factors for Preterm Birth in the state of Qatar: A Population-based Study - Salama E, Elsayed Ibrahim Ali Salama; Salama, husam salama; Alobaidly , Sawsan Hassan (Acta Biomedica Atenei Parmensis, 2021)
Objectives: To review the demographics and socioeconomic determinants of preterm birth (PTB) compared to term births among the Qatari population. Methods: This was a retrospective data analysis of 59,308 births. Data were retrieved from a Population-based Cohort Study. Data were gathered from the PEARL-Peristat maternal newborn registry for 2011, 2012, 2017, and 2018. We compared the preterm births group (delivery < 37 weeks) with the term group (delivery ≥ 37 weeks) regarding socioeconomic factors, including maternal nationality, religion, level of education, mother’s occupation, family income, housing, consanguinity, early childbearing, high-risk pregnancy, smoking, assisted conception, antenatal care, and place of delivery. Results: The prevalence of preterm birth was 9%. There were more Saudi nations in the preterm group compared to term (33% vs. 28%, p-value < 0.001). There were more preterm births than term births among working mothers (40% vs. 35%), high-risk pregnancies (24% vs. 18%), those that has used assisted conception (18% vs. 3%), those without antenatal care (11% vs. 5.6%), and those delivered in a tertiary women hospital (88.5% vs. 84.5%) (all p-values < 0.001). There were more women living in villas (41% vs. 38%, p = 0.01) and more smokers (0.8% vs. 0.5%, p = 0.030) in the preterm group than in the term group. There were no differences between the two groups regarding religion, level of maternal education, family income, and early childbearing. Conclusion:In our population, we identified several factors associated with preterm births, the most important is Lack of antenatal care , assisted conception and working mothers.